2023
DOI: 10.1093/cei/uxad034
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of MALAT1 is a hallmark of tissue and peripheral proliferative T cells in COVID-19

Abstract: T cells play key protective but also pathogenic roles in COVID-19. We studied expression of long non-coding RNAs (lncRNAs) in COVID-19 T cell transcriptomes by integrating previously published single-cell RNA sequencing datasets. The long intergenic non-coding RNA MALAT1 was the most highly transcribed lncRNA in T cells, with Th1 cells demonstrating the lowest and CD8+ resident memory cells the highest MALAT1 expression, amongst CD4+ and CD8+ T cells populations, respectively. We then identified gene signature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…The effect of Malat1 on myeloid cell populations in the TME in vivo led us to investigate T-cell infiltration and function within the immune landscape because the T-cell response is paramount for the efficacy of immunomodulation therapies. A recent study in COVID-19 patients found that decreased Malat1 expression in T cells was linked to increased proliferative capabilities ( 54 ). However, there is little known about the effect Malat1 inhibition has on T-cell infiltration and function in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of Malat1 on myeloid cell populations in the TME in vivo led us to investigate T-cell infiltration and function within the immune landscape because the T-cell response is paramount for the efficacy of immunomodulation therapies. A recent study in COVID-19 patients found that decreased Malat1 expression in T cells was linked to increased proliferative capabilities ( 54 ). However, there is little known about the effect Malat1 inhibition has on T-cell infiltration and function in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we identi ed three effector Treg clusters among CCR7 low cells expressing HLA-A, CD74, and IL32, respectively. An additional Treg cluster was de ned by high MALAT1 expression, which is associated with the cell cycle phase and Treg proliferation 29,30 . Lastly, we identi ed a subset of Tregs expressing Humanin genes MTRNRL28 and MTRNRL12.…”
Section: Single-cell Rna-seq Identi Es Treg Subsets In Gdm and Health...mentioning
confidence: 99%
“…This cluster has been previously reported and suggested to include cells which are poised to rapidly respond to secondary infections by producing cytokines 42,43 . Quiescent memory cells were slightly more prevalent within NT and characterized by the expression of several long non-coding RNAs (including Malat1) 44,45 and low ribosomal gene expression. A small proportion of our CD4 TRM was naïve-like T cells expressing Ccr7, Sell and Klf2 46 .…”
Section: Cd4 Trm In the Lungs And Nt Are Heterogeneous But Th17 Cells...mentioning
confidence: 99%